A translation from "Pavan" into English of Angelo Beolco's Parlamento de Ruzante, qual giera sto in campo : Ruzante's Discourse on coming back from the battlefield : a re-edition of a famous Italian 16th century play based on Verona Civica ms. 36 - Ruzzante, 1502?-1542.; Fanelli, Carlo; Trumper, John. (Lewiston : Edwin Mellen Press, 2012)
The present study is divided into three parts, the first of which is an in-depth introduction by Carlo Fanelli to the authors and problems of 16th century Renaissance Italian dialect comedy and the relevance of a playwright such as Angelo Beolco (RUZANTE). Particular attention is paid to the comedy from the point of view of the social problems presented by veterans or deserters after long and socially disastrous wars. The second part is a short introduction to the manuscript history of RUZANTE's dialect comedy El Parlamento prior its printing by Stefano Alessi at Venice in 1551. The Verona Cod.
3. The Parlamento and Bilora. A Tragi-comic Diptych4 -- The Parlamento: History, Dramaturgical Texture, Language, Charatcters; 5 -- From Venice to Europe. The Parlamento's Performances from '500 to '900; 6 -- Modern Editions of the Parlamento; Quoted Studies (Parts I & II); Part III; 1 -- The editions; 2 -- The language; Quoted Studies (Part III); Part IV; II Parlamento; Notes to the 'Pavano' Text of the Play.
Print version record.
eBooks on EBSCOhost
Keywords: Ruzzante, -- 1502?-1542 -- Translations into English; Ruzzante, -- 1502?-1542; Italian drama (Comedy) -- History and criticism; Italian drama -- To 1700 -- History and criticism; Dialect drama, Italian -- History and criticism; Comédie italienne -- Histoire et critique; Théâtre italien -- Jusqu'à 1700 -- Histoire et critique; DRAMA -- Continental European; Dialect drama, Italian; Italian drama; Italian drama (Comedy); To 1700; Criticism, interpretation, etc; Translations